Evaluation of endometrial carcinoma prognostic immunohistochemistry markers in the context of molecular classification. (14th October 2017) - Karnezis, Anthony N; Leung, Samuel; Magrill, Jamie; McConechy, Melissa K; Yang, Winnie; Chow, Christine; Kobel, Martin; Lee, Cheng-Han; Huntsman, David G; Talhouk, Aline; Kommoss, Friederich; Gilks, C Blake; et al.
Abstract: Molecular subclassification of endometrial carcinoma (EC) with Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) identifies four subtypes [DNA polymerase epsilon ( POLE ) mutant, mismatch repair‐deficient, p53 wild‐type (wt), and p53 abnormal]. The aim of this study was to evaluate additional EC biomarkers in the context of these subtypes. Tissue microarrays encompassing 460 previously characterized ECs were assessed for L1‐cell adhesion molecule (L1CAM), progesterone receptor (PR), estrogen receptor (ER) alpha, stathmin, and phosphatase and tensin homolog (PTEN), by immunohistochemistry (IHC). Associations with clinicopathological parameters, molecular subtype, and outcomes were determined. About 413 ECs (75% endometrioid, >15% serous) had complete data. L1CAM overexpression was found in 16%, associated with older age, lower body mass index (BMI), advanced stage, grade 3 (97%), non‐endometrioid histology (84%), deep myometrial invasion, lymphovascular space invasion (LVSI), and ER‐negative, PR‐negative status. Tumours overexpressing L1CAM were associated with poor outcomes hazard ratio (HR) [95% confidence interval (CI)] 3.35 [2.10–5.23] for disease‐specific survival [DSS], p < 0.0001. PR positivity was associated with younger women, higher BMI, early stage (77% stage I), low grade (61%), endometrioid histology (90%) without LVSI or nodal disease, ER positivity (90%), p53wt tumours (55%), and favourable outcomes [HR (CI) 0.39 (0.25–0.62) for DSS, p < 0.0001]. ER positive tumours were early stage (73%), low grade, endometrioid histology, with improved DSS. Stathmin and PTEN IHC were not associated with outcomes. There was minimal agreement between IHC and mutation status for PTEN . L1CAM overexpression was significantly associated with the p53 abnormal molecular subtype, which accounted for more than 70% of the tumours overexpressing L1CAM. PR expression also correlated with molecular subtype, with most PR negative tumours being p53 abnormal. Multivariable analysis demonstrated that only ProMisE subtype [overall survival (OS), DSS, and progression‐free survival] and age (OS only) maintained an association with outcomes. The prognostic significance of the single biomarkers tested could be explained based on their being covariable with the ProMisE molecular subtype.